Mātauranga Māori framework for surveillance of plant pathogens - Wood, Waitangi; Lustig, Audrey; Latham, Maria C.; Anderson, Dean P. (Frontiers in Forests and Global Change, 2024)
Faced with growing biosecurity risks and threats, countries worldwide seek to protect their biodiversity from ecosystem degradation and loss. Biosecurity surveillance of plant pathogens and the diseases they cause is fundamental for management and eradication of these risks. To date, the surveillance systems in Aotearoa New Zealand have reflected empirical scientific principles and have been largely devoid of mātauranga and te ao Māori, which have seldom been regarded as valid or relevant knowledge systems to inform biosecurity. Because of this, mana whenua themselves have been disconnected from these systems. The inclusion of mana whenua and their mātauranga is important, not only to recognise their role and rights as indigenous peoples of Aotearoa New Zealand, but because it is through place-based approaches that better biodiversity and environmental outcomes can be achieved. Here, we describe a mātauranga Māori framework for surveillance (MMFS) of plant pathogens, which introduces the principles and methodologies that aim to elevate mana whenua and mātauranga research into the biosecurity and science systems. The MMFS facilitates the co-existence of mātauranga and empirical scientific knowledge without the need for inter-dependent validation, on the assumption that this will lead to better research and operational outcomes. It addresses issues around data ownership and sovereignty, informed consent, and cultural licence. We present a case study where the MMFS has been applied to research initiatives aimed at addressing myrtle rust and kauri dieback in Aotearoa New Zealand. The MMFS informed the development of a data storage platform, which anchors data to the place of origin, recognising its provenance and giving effect to Māori data sovereignty. This process ensures mana whenua have timely access and use of existing and emergent data. Following the principles of the MMFS, we developed and used a “proof of pathogen absence” tool to co-design with mātauranga environmental experts a risk-based surveillance plan for the purpose of demonstrating freedom from disease in areas where a pathogen has not been detected. The MMFS provides a way of planning and implementing environmental surveillance that can be applied to the full range of environmental problems internationally where indigenous populations are involved.